DESIGNING OF FEMALE ENSEMBLE IN THE MILITARY STYLE - Засорнова, І. О.; Краснюк, Л. В.; Журавльова, Х. О. (Art and Design, 2020)
Projecting and manufacturing of a women's clothing ensemble in the military-style based on the analysis of the uniform of soldiers of the Armed Forces of Ukraine. In the process of the research the basic principles of the systematic approach to the design-projecting of the women's clothing ensemble were used: literary-analytical researches, combinatorics method. Historical prerequisites for the appearance of the style of military uniforms in clothing are determined. The characteristic features and basic principles of creating military-style clothing are identified. The collections of modern designers are investigated and the main directions of development of military style in women's clothing are highlighted. The results of the artistic design of the military-style women's clothing ensemble are presented and its artistic and compositional features are described. The main artistic and compositional features of the military style in modern women's clothing are identified, which is the basis for designing the author's ensemble of women's clothing in this style. The main artistic and compositional features of the military style in modern women's clothing are identified, which is the basis for designing an author's ensemble of women's clothing in this style. The analysis of structural and technological elements of military uniform was performed on the following features: silhouette, type of clasp, sleeve cover, neck and collar design, design of the lower sleeves, type and location of pockets, functional and finishing details, areas of application of distinctive marks, color, fittings. Practical recommendations are given about the choice of artistic and compositional solutions, structural and technological elements, selection of materials, accessories, hats and shoes in the design of military-style women's clothing. The author's ensemble of women's clothing in the military style named "Pentesileya" has been created.